2003
DOI: 10.1159/000070430
|View full text |Cite
|
Sign up to set email alerts
|

Oral Allergy Syndrome to Chicory Associated with Birch Pollen Allergy

Abstract: Background: A few cases of IgE-mediated chicory allergy with oral, cutaneous, and/or respiratory symptoms are reported. We present 4 patients with inhalant birch pollen allergy and oral allergy syndrome to chicory. IgE-binding proteins in chicory and cross-reactivity with birch pollen were studied. Methods: Chicory extract was prepared and immunoblotting was used to study IgE reactivity and cross-reactions with birch pollen. Results: The pattern of IgE binding to chicory was variable among the patients, with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Cadot et al [21] reported on four subjects with OAS due to non-occupationally acquired chicory sensitization. He demonstrated that although those patients were sensitized to birch pollen and Bet v 1, other allergens could be the cause of their symptoms.…”
Section: Allergenic Sources and Molecules Causing Oral Allergy Syndromementioning
confidence: 99%
“…Cadot et al [21] reported on four subjects with OAS due to non-occupationally acquired chicory sensitization. He demonstrated that although those patients were sensitized to birch pollen and Bet v 1, other allergens could be the cause of their symptoms.…”
Section: Allergenic Sources and Molecules Causing Oral Allergy Syndromementioning
confidence: 99%
“…They described that although chicory root gives a pleasant aroma when added to tea, it acts like a sedative on the central nervous system and could impair reaction time in some individuals. Besides, chicory can also trigger oral, cutaneous, and/or respiratory symptoms [ 20 ], and for that reason, its use as a non-declared adulterant in tea is prohibited.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70% of patients who are allergic to birch pollen may experience symptoms after consumption of foods from these groups. 3,4 Likewise, IgE cross-reactivity has been identified be-tween house dust mites and snails. 5 The so-called latex-fruit syndrome also is a well-documented phenomenon in crossreactive allergies.…”
mentioning
confidence: 99%